Renal tubular disease in the era of combination antiretroviral therapy. (10th September 2015) - Hamzah, Lisa; Booth, John W.; Jose, Sophie; McAdoo, Stephen P.; Kumar, Emil A.; O'Donnell, Patrick; Hilton, Rachel; Sabin, Caroline; Williams, Deborah I.; Jones, Rachael; Post, Frank A.
<x xml:space="preserve">Abstract</x> Objectives: To describe the spectrum of renal tubular disease (RTD) in HIV-positive patients and its association with exposure to antiretroviral therapy (ART). Design: Review of 265 consecutive renal biopsies from HIV-positive patients attending eight clinics in the United Kingdom between 2000 and 2012. Methods: We described the clinical characteristics of patients with RTD and compared current/recent exposure (at the time of, or up to 3 months prior to the date of biopsy) to potentially nephrotoxic ART [tenofovir (TDF), atazanavir (ATV), indinavir (IDV) and lopinavir/ritonavir (LPV/r)]. We also analysed the incidence of RTD in the UK CHIC cohort. Kruskall–Wallis, analysis of variance and Fisher's exact tests were used to evaluate between-group differences. Results: Of the 60 RTD cases, 54 (90%) were included in the analyses. RTD comprised of three distinct patterns: acute tubular injury (ATI, n = 22), tubulo-interstitial nephritis (TIN, n = 20) and interstitial fibrosis and tubular atrophy (IFTA, n = 12). Compared with TIN and IFTA, ATI cases were less likely to be of black ethnicity (10 vs. 42–55%; P = 0.006), more likely to be on ART (100 vs. 55–68%; P = 0.001), with HIV-RNA below 200 copies/ml (100 vs. 54–58%; P < 0.001), and more likely to have current/recent exposure to TDF (P < 0.001). We did not find evidence for an association between exposure to TDF, ATV/r or LPV/r and either TIN or IFTA. Conclusion: RTD was present in approximately 20% of renal biopsies and comprised three distinct injury patterns with considerable clinical overlap. ATI was associated with TDF exposure, although the overall incidence of biopsy-defined ATI was low.